Accelerating quality upgrading in Ugandan dairy value chains - Van Campenhout, Bjorn (International Food Policy Research Institute, 2024)
Uganda’s dairy sector has grown significantly over the past two decades, yet challenges in milk quality continue to hinder its potential. A recent study by Richard Ariong and colleagues explores interventions to address these challenges through field experiments targeting Milk Collection Centers (MCCs) and farmers that deliver to these MCCs. The findings provide valuable insights on quality upgrading in value chains in developing countries.